Meningkatkan Kemandirian Anak Usia 5-6 Tahun Sesuai Profil Pelajar Pancasila Dengan Menggunakan Media Gambar AI Di Tk-It Al-Ikhlas Kota Binjai Tahun Ajaran 2023-2024 - Megawati, Neni; Marbun, Sariana (JURNAL BUNGA RAMPAI USIA EMAS, 2024)
This research was carried out with the aim of increasing the independence of children aged 5-6 years according to the Pancasila student profile using AI image media at Kindergarten-It Al-Ikhlas, Binjai City for the 2023-2024 academic year. This research is a type of classroom action research with 12 subjects, of which 6 are men and the other 6 are women. The object of this research is increasing children's independence as Pancasila students aged 5-6 years at Al-Ikhlas IT Kindergarten in Binjai City for the 2023/2024 academic year. The data collection method is carried out by observation. The data analysis technique is Descriptive Percentage. The findings in efforts to increase children's independence in cycle 1 were 70.5% in the good category, while in cycle 2 it was 83.9% in the Very Good Category. Meanwhile, the results of teacher observations in cycle 1 were 75%. The results of teacher observations in Cycle 2 were 84.4%, which is in the Very Good category. Based on the results obtained, image media can increase the independence of children aged 5-6 years according to the Pancasila student profile